Determinants of overweight/obesity among reproductive age group women in Ethiopia: multilevel analysis of Ethiopian demographic and health survey - Yigizie Yeshaw; Sewnet Adem Kebede; Alemneh Mekuriaw Liyew; Getayeneh Antehunegn Tesema; Chilot Desta Agegnehu; Achamyeleh Birhanu Teshale; Adugnaw Zeleke Alem (BMJ Open, 2020)
Objective Overweight/obesity among women is associated with an increased risk of gestational diabetes, pre-eclampsia, postpartum haemorrhage, low birth weight, congenital malformation and neonatal deaths. Although the magnitude of overweight and obesity among the reproductive age group women is a common problem in Ethiopia, there are limited studies that determine the associated factors of overweight and obesity at the national level. Therefore, this study aimed to identify the determinant factors of overweight/obesity among reproductive age group women in Ethiopia.Design Cross-sectional study design.Setting Ethiopia.Participants Non-pregnant women aged 15–49 years.Primary outcome Overweight/obesity.Methods The present study used the Ethiopia Demographic Health Survey (EDHS) data for 2016. A total of 10 938 non-pregnant reproductive age group women were included in the analysis. Both bivariable and multivariable multilevel logistic regression were performed to determine the determinants of overweight and obesity among women in Ethiopia. The OR with a 95% CI was estimated for potential determinants included in the final model.Results Those women with secondary education (adjusted OR (AOR)=1.48, 1.01, 2.18), higher education (AOR=1.78, 1.13, 2.81), richer (AOR=1.85, 1.15, 2.98) and richest wealth index (AOR=3.23, 1.98, 5.29), urban residence (AOR=4.46, 2.89, 6.87), married (AOR=1.79, 1.21, 2.64), widowed (AOR=2.42, 1.41, 4.15), divorced (AOR=1.84, 1.13, 3.00), aged 25–34 years (AOR=2.04, 1.43, 2.89), 35–44 years (AOR=2.79, 1.99, 3.93) and 45–49 years (AOR=2.62, 1.54, 4.45) had higher odds of developing overweight and obesity.Conclusion Women with higher education level, high wealth status, older age, formerly married and those urban dwellers had higher odds of overweight and obesity. Therefore, regular physical activity, reducing consumption of fat/energy-dense food as well as modifying the mode of transportation is recommended.